2014
DOI: 10.1111/j.2047-2927.2014.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural changes in psychogenic erectile dysfunction patients

Abstract: SUMMARYBrain dysfunction in erectile dysfunction (ED) has been identified by multiple neuroimaging studies. A recent MRI study indicated grey matter alterations in ED patients. This study aims to investigate the microstructural changes of cerebral white matter (WM) in psychological ED patients and their possible correlations with clinical variables. Twenty-seven psychological ED patients and 27 healthy subjects (HS) were included and underwent a magnetic resonance (MR) diffusion tensor imaging (DTI) scan. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…Moreover, it has been found that negative CTh correlations are not mediated by direct fiber connections [Gong et al, 2012]. Therefore, the negative correlations observed in this work might concur with the observation of impaired WM fiber connectivities in pED [Zhang et al, 2014].…”
Section: Altered Structural Covariance Network Organization In Pedsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, it has been found that negative CTh correlations are not mediated by direct fiber connections [Gong et al, 2012]. Therefore, the negative correlations observed in this work might concur with the observation of impaired WM fiber connectivities in pED [Zhang et al, 2014].…”
Section: Altered Structural Covariance Network Organization In Pedsupporting
confidence: 90%
“…The neurobehavioral components of male SA are conceived as closely interrelated and coordinated [Stoleru et al, ]. The reported WM microstructural alterations in pED [Zhang et al, ] might indicate neuroanatomical connectivity abnormalities. Therefore, we predict that the pathology of pED may be also correlated with abnormal cortical structural network architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased connectivity was observed in the posterior cingulate cortex, inferior parietal lobes and medial prefrontal cortex of the nED patients compared to the connectivity in the healthy controls, whereas decreased and increased connectivity was observed in the anterior cingulate cortex and the right insula, respectively. Zhang et al reported microstructural differences in white matter between healthy controls and nED patients (Zhang et al, ). Grey matter atrophy of the bilateral nucleus accumbens and left hypothalamus has also been reported in nED patients (Cera et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on the brain MRI of psychogenic ED [7,[19][20][21][22][23][24][25][26][27][28][29][30][31]. Despite significant progress, the mechanism aiming at CNS targets treated by tadalafil is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Normal erectile function is a result of the harmonious regulation and control of the central nervous system (CNS), which includes the supraspinal centres, the spinal cord and peripheral nerves. In the last two decades, exploring the role of CNS in sexual arousal by functional and structural neuroimaging studies, the magnetic resonance imaging (MRI) [20] such as diffusion tensor imaging (DTI) [21,[23][24][25], functional MRI (fMRI) and resting-state fMRI attracted many researchers [23][24][25]. Since 2002, compared with healthy subjects (HS), much researchers have found that psychologic ED patients showed significant changes in cerebral functions.…”
Section: Introductionmentioning
confidence: 99%